Al-Muqallal from the Narrators their Impact and the Degree of their Speech - Attia , Mossadaq (Islamic Sciences Journal, 2023)
Al-Muqallal " Persons to whom few prophetic traditions are ascribed" among the narrators of the Prophet's hadith are those who narrated very few hadiths to the point where the narrations of some of them included only a single hadith called the singulars and the individuals, and some of them are called strange because there is no other suitable way for them. Some scholars have included in the name Al-Muqaloon those who only one of the narrators narrated about them. special topic was devoted to them, however they were treated like the treatment of other narrators except in terms of tabulating the Musnad (which are books that arrange hadiths on the names of the narrators of the Companions), for the purpose of collecting their hadiths in one place, and this is in all classes of Companions, Taabi'een and followers . In this research, we will learn about the mechanism of dealing with them and their narrations by the scholars of the Prophet’s hadith, and the impact they left on the narration and the degree of their hadith in terms of health, improvement, weakness and status.